The Role of Strategic Flexibility on Business Survival - Harisatul Agustin; Syarifa Hanoum; Tasya Arihul Wardah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
The COVID-19 pandemic has had severe consequences across various aspectsof life, significantly impacting the culinary sector, which is a crucial part of thetourism industry. Restrictions on dine-in services compelled businesses toadapt to take-out options, resulting in significant repercussions. To navigatethese challenging times and ensure the survival and growth of the culinaryindustry, entrepreneurs and restaurant managers had to adopt innovativestrategies. Income reductions affected nearly 43% of culinary businessesduring this period. To investigate the dynamics further, the research conducteda PLS-SEM analysis, surveying 163 MSME owners or restaurant managersoperating in the Surabaya city region, who had received government supportand continued their business operations amidst the pandemic. The analysisrevealed that strategic flexibility played a pivotal role in influencing marketinginnovation and process innovation. However, the impact of marketinginnovation on business survival was not direct, while process innovationsignificantly influenced business survival. Interestingly, the study observedthat government support did not alter the relationships between marketinginnovation, process innovation, and business survival.